The LeChatelier Principle - Milgrom, Paul; Roberts, John (American Economic Review, 1996)
Forthcoming in the American Economic Review The LeChatelier principle, in the form introduced into economics by Samuelson, asserts that at a point of long-run equilibrium, the derivative of long-run compensated demand with respect to own price is larger in magnitude than the derivative of short-run compensated demand. We introduce an extended LeChatelier principle that applies also to large price changes and to uncompensated demand as well as to a wide range of concave and nonconcave maximization problems outside the scope of demand theory. This extension also clarifies the intuitive basis of the principle. JEL classification numbers: C60, D10, D20.